Neurobehavioral phenotypes of delay discounting and cognitive control in child attention‐deficit/hyperactivity disorder and obesity: Shared or distinct? - Thapaliya, Gita; Carnell, Susan; Mostofsky, Stewart H.; Rosch, Keri S. (Pediatric Obesity, 2023)
Summary: Background: Attention‐deficit/hyperactivity disorder (ADHD) and obesity have been independently associated with deficient cognitive control (CC) and heightened preference for immediate reward. Objectives: We aimed to identify specific shared and distinct neurobehavioral phenotypes of child obesity and ADHD by simultaneously measuring CC and preference for immediate reward in children with and without ADHD who varied in body weight. Methods: This case–control study included 323 8–12 year olds (ADHD n = 215, typically developing (TD) screened for ADHD symptoms [TD] controls n = 108) varying in body weight. Children completed a go/no‐go task (assessing CC), as well as a classical money delay discounting (DD) task and novel experiential game time DD task (assessing preference for immediate over delayed rewards). Results: For game time DD, there was a body mass index z‐score (BMIz)*ADHD interaction, such that TD children with overweight/obesity showed game time DD levels that were greater than those of TD children without overweight/obesity and similar to those of children with ADHD. Only children with ADHD showed poorer CC compared to TD children, with no effects of body weight. Conclusions: Heightened game time DD with delays and rewards experienced in real‐time may represent a neurobehavioral phenotype that is shared between ADHD and overweight/obesity in childhood, whereas deficient CC may be specific to children with ADHD.